From Scientists' Fear to Knowledge Dialogue (2014)
In this article, Yulieth Hillón Vega, doctor in Legal Sociology and Political Institutions, recounts her experience of interdisciplinary work as an advisor of the workshop Why do we feel fear? which is part of the first stage of EAFIT Children's University.